Early onset and rapid progression of glaucoma in a neonate with Sturge-Weber syndrome - Suthida Chaithirayanon (2018)
Sturge-Weber syndrome (SWS) is an uncommon neurocutaneous syndrome usually presenting with a triad of cutaneous, neurological, and ophthalmological symptoms. The cutaneous lesion can be observed at birth in most cases while the symptoms of the nervous and ocular systems involvement usually appear later in life. The most common ocular manifestation in SWS is glaucoma, which can occur in the early-life period. The authors reported a case of SWS in which the symptoms of glaucoma rapidly developed within two weeks following an ophthalmologic evaluation that was initially negative at the age of one week.